Association between disease activity and HALP score in ankylosing spondylitis patients - Cüre, Osman (The European Research Journal, 2025)
Objective: The goal of this research was to assess HALP score (Hemoglobin, Albumin, Lymphocyte, Platelet) as a potential indicator of disease activity among patients with Ankylosing Spondylitis (AS). Methods: Data from 260 individuals (130 AS patients and 130 healthy controls) were retrospectively reviewed. Clinical and demographic information was collected, and the AS group was divided into remission and active disease subgroups for comparison. Results: In contrast to the group of healthy controls, AS patients had a lower HALP score (P<0.001). The HALP score was notably lower in the active patient group than in the remission group (P=0.025). The HALP score and the erythrocyte sedimentation rate were found to be negatively correlated (r=-0.307, P<0.001). Additionally, significant negative correlations were identified between the HALP score and the following parameters: Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) (r=-0.208, P=0.017), Bath Ankylosing Spondylitis Functional Index (BASFI) (r=-0.195, P=0.026), Ankylosing Spondylitis Disease Activity Score using C-reactive protein (ASDAS-CRP) (r=-0.199, P=0.024), and Visual Analog Scale (r=-0.229, P=0.009). The optimal HALP score cut-off for determining disease activity was established as ≤0.56 (AUC: 0.619, 95% CI: 0.518-0.721, sensitivity: 80.00%, specificity: 40.00%). Conclusions: This study found that the HALP score was lower in active AS patients compared to those in remission. Therefore, the HALP score may serve as a potential marker for assessing disease activity in AS patients.